Mesenchymal Stem Cells for the Treatment of Complex Anovaginal and Rectovaginal Fistulas in Crohn's Disease: A Systematic Review - Martins, Kleuber Arias Meireles; Faria, Isabela Coutinho; Cardoso, Leonardo Januário Campos; Gontijo, Pedro Henrique Gibram; Bittarães, Ana Júlia da Silva Oliveira; Corcinio, Mariana Menezes; Braga, Bárbara Nogueira; de Jesus, Mariana Lisboa (Journal of Coloproctology, 2025)
To evaluate the efficacy and safety of mesenchymal stem cells (MSCs) for treating complex anovaginal and rectovaginal fistulas in Crohn's disease (CD) patients through a systematic review.This review adhered to PRISMA and Cochrane guidelines. Literature searches were conducted on PubMed, Cochrane Library, Embase, and Web of Science using a PICO framework (P: CD patients with complex fistulas; I: MSC therapy; C: conventional treatments; O: efficacy and safety). Keywords included “stem cell,” “fistula,” and “Crohn's disease.” Articles were screened via the Rayyan® platform for inclusion based on eligibility criteria, with conflicts resolved by consensus.Of 1,197 records, 7 studies met inclusion criteria. MSC therapy demonstrated variable healing rates ranging from 50% to 75%, with low adverse event profiles. Studies highlighted therapeutic potential in reducing fistula drainage and promoting tissue regeneration. However, significant heterogeneity in patient populations, MSC doses, and study methodologies complicated outcome standardization. A meta-analysis reported fistula healing rates of 58–62% and clinical remission of 62.52%, superior to conventional therapies. Factors such as disease severity, prior treatments, and anatomical differences influenced outcomes.MSCs offer promising treatment for complex fistulas in CD, demonstrating favorable safety and efficacy. However, variability in study designs, dosing protocols, and patient profiles underscores the need for standardized methodologies and larger clinical trials. Optimizing MSC use, particularly as a first-line therapy, could enhance outcomes and provide a viable alternative to conventional surgical approaches.
Keywords: stem cell; fistula; Crohn's Disease